ENSURING JUDICIAL INDEPENDENCE BY EVALUATING THE RECRUITMENT PROCESS AND LEGAL FRAMEWORK FOR JUDGES IN INDONESIA - Sukmariningsih, Retno Mawarini; Nurudin, Agus; Irawan, Benny Bambang; Riyanto, Ontran Sumantri (UNISSULA, 2024)
As the highest judicial institution, the Supreme Court exercises its powers freely and independently. Judges must have morals, principles of justice, and adhere to a code of ethics. Judges must uphold justice in resolving disputes or legal cases and ensure that society receives justice. As state officials, the recruitment process for judges should be separated from the recruitment of civil servants. The position of judges as state officials should be regulated comprehensively by law. This research examines the recruitment process of judges as independent implementers of judicial power. The research method used is descriptive, using qualitative data analysis with a normative juridical approach. Supreme Court Regulation Number 1 of 2021 concerning Amendments to Supreme Court Regulation Number 2 of 2017 concerning the Procurement of Judges regulates the need for judges in General Courts, Religious Courts and State Administration through the acceptance of Candidates for Civil Servants that needs to be improved. This need arises because there are no legal provisions regarding the recruitment of judges as state officials. In the future, provisions for the recruitment of judges should be regulated through Government Regulations so as not to impact the independence of judges as implementers of judicial power.